Evaluation of In Vitro Antimalarial Activity of Different Extracts of Eremostachys azerbaijanica Rech.f. - Asnaashari, Solmaz (Iran J Pharm Res, 2016)
Six extracts with different polarity from aerial parts and rhizomes of Eremostachys azerbaijanica Rech.f., were screened for their antimalarial properties by cell free -hematin formation assay. Dichloromethane (DCM) extracts of both parts of plant showed significant antimalarial activities with IC(50) values of 0.949 ± 0.061 mg/mL in aerial parts and 0.382 ± 0.011 mg/mL in rhizomes. Bioactivity-guided fractionation of the most potent part (DCM extract of rhizomes) by vacuum liquid chromatography (VLC) afforded seven fractions. Two fractions [100% Ethyl acetate (EtOAC) and 100% Methatol (MeOH)] showed considerable antimalarial activity with IC(50) values of 0.335 ± 0.033 mg/mL and 0.403 ± 0.037 mg/mL, respectively. According to GC-MS analysis, the sesquiterpene, steroid and coumarin derivatives are the main constituents of the most potent fractions; therefore, it seems that the anti malarial activity of these fractions may be related to the presence of these types of compounds.